Wiskott Aldrich Syndrome, often Missed: A Case Report and Review - Kumar, Mani Kant; Narayan, Raghvendra (Journal of Nepal Paediatric Society, 2011)
Wiskott-Aldrich syndrome is an X-linked recessive disorder characterized by thrombocytopenia, eczema and recurrent infections. We report a 15 month old boy who had presented with lower gastrointestinal bleed, recurrent infections and eczema. Blood picture revealed microthrombocytopenia, high IgA and IgE, and low IgM and Normal IgG levels. A diagnosis of Wiskott-Aldrich Syndrome was made, which was missed by many paediatrician even after prolonged hospital stay before admission in our Institute. The recent progress in understanding of the pathophysiology and treatment are discussed. Key words: Wiskott-Aldrich syndrome; Eczema; Microthrombocytopenia DOI: 10.3126/jnps.v31i2.4122 J Nep Paedtr Soc 2010;31(2):146-150